Pandemi Covid-19: Eefektivitas Pembelajaran dalam Jaringan - Puji Rahayu, Tatik; Fadloli Al Hakim, Muhammad; Ibda, Hamidulloh (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2021)
This study aimed to analyze the implementation effectiveness of the learning from home (BDR) process during the Covid-19 pandemic in grade V of MI Muhammadiyah Botoputih Tembarak. This research used mix method. The data collection technique used was a questionnaire given to the students once a month. The subjects of this study were the students of grade V at MI Muhammadiyah Botoputih Tembarak. Based on the results of research conducted by filling out questionnaires, in general, the implementation of learning from home (BDR) in the sixth-grade students of MI Muhammadiyah Botoputih Tembarak run quite effectively with a percentage of 60-79%. The results of the BDR learning implementation questionnaire which had bad effectiveness with the criteria of 48% were in the evaluation process. It is suggested in learning from home (BDR), teachers are required to be able to design learning activities from planning to evaluating in a simpler, more creative and effective way